The Effects of Leaders’ Capabilities on the Performance of Self-Help Groups in Suna West Constituency, Migori County, Kenya - Masara, Peter Francis; Kiiru, Macmillan; Kariuki, Emilio (International Journal of Humanity and Social Sciences, 2025)
Purpose: The purpose of this study was to determine the effect of leadership capabilities on the performance of Self-Help Groups (SHGs) in Suna West Constituency. Methodology: Utilizing a descriptive research design, the study targeted 1,510 members across 80 SHGs, with a sample size of 306 members determined using the Krejcie and Morgan (1970) formula. Data were analyzed using SPSS for quantitative statistics, such as percentages and means, while qualitative data were examined thematically. Findings: Findings reveal that innovativeness is present in self-help groups (SHGs), with 60% acknowledging change management mechanisms. However, opinions are divided on whether leaders value member contributions, as 39.8% agree and an equal percentage disagree. While 81.7% of SHGs have job descriptions, 40% report inconsistencies in task assignments, indicating a need for better delegation. Self-awareness among leaders is also notable, with all members feeling empowered to voice concerns and 80% of leaders welcoming feedback. Unique Contribution to Theory, Practice and Policy: The study concludes that leadership characterized by innovativeness, effective task management, and a clear vision is essential for enhancing SHG performance, recommending ongoing training for leaders to foster growth. This study uniquely contributes to theory by linking leadership dimensions to SHG performance and informs policy by advocating for targeted training programs to enhance leaders' skills.